Mangrove Conservation, Ecotourism, and Development Strategy in Bandar Bakau Dumai, Indonesia - EFFENDI, Irwan; YOSWATY, Dessy; HARAHAP, Irawan; JUPENDRI, Jupendri; ANDRIZAL, Andrizal (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).19, 2022)
Mangrove ecosystems have components of landscapes, flora, fauna, and local communities to form a unified ecosystem. Bandar Bakau Dumai (BBD) is a mangrove conservation and ecotourism area located on the outskirts of Dumai City, Indonesia. This study aimed to analyze the current and past conditions of the area and develop strategies for developing it in the future. The research was carried out by observing, interviewing, non-structured in-depth interviewing, and studying literature. The condition and potential of the mangrove ecotourism area were analyzed from the attractiveness, infrastructure, facilities and services, market potential, institutional elements, and socio-economic conditions of the community. The development strategy is formulated using a SWOT (strength, weakness, opportunity, and threat) analysis by systematically identifying various factors to determine the priority of the development strategy. The BBD conservation area is still relatively good and has not changed from previous years. However, the role of mangrove ecotourism is far removed. The supporting facilities and infrastructure are generally not maintained. The following recovery and development strategies are recommended: increasing human resource capacity; strengthening the role of the government, industry, and sponsors in the development of facilities and infrastructure; proper promotion and marketing; and varying ecotourism services and products; and construction coastal abrasion protectors.